2011
DOI: 10.3382/ps.2010-01235
|View full text |Cite
|
Sign up to set email alerts
|

Immune response gene expression in spleens of diverse chicken lines fed dietary immunomodulators

Abstract: Vaccines, antibiotics, and other therapeutic agents used to combat disease in poultry generate recurring costs and the potential of residues in poultry products. Enhancing the immune response using alternative approaches such as selection for increased disease resistance or dietary immunomodulation may be effective additions to the portfolio of strategies the industry applies in poultry health management. The objective of this study was to characterize the effects of dietary supplementation with 3 immunomodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Nevertheless, no significant differences were observed in spleen or ileum in our study. Similarly, Kumar et al [62] identified that β-glucan in 0.10% could not alter TLR-4 mRNA expression in chicken spleen; however, no LPS challenge was involved in that study. Gene expression level of TLR-5 in this study was not altered significantly among the treatments.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, no significant differences were observed in spleen or ileum in our study. Similarly, Kumar et al [62] identified that β-glucan in 0.10% could not alter TLR-4 mRNA expression in chicken spleen; however, no LPS challenge was involved in that study. Gene expression level of TLR-5 in this study was not altered significantly among the treatments.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Markazi et al [9] found yeast cell wall products could not affect inflammatory IL-1β mRNA expression in chicken cecal tonsils under a coccidial challenge. Kumar et al [62] also discussed that β-glucan treatment did not produce different expressions of IL-1β, TLR-4 and TLR-5 in chicken spleen compared to LPS challenged birds. However, this study shows β-glucan supplementation could decrease the ileal gene expression level of TLR-5 compared to anthocyanin-fed birds.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most recent studies are synthesized in Table 6 . Dietary immunomodulation is a key to enhance the productivity and immune system integrity of farm animals raised under the absence of antibiotics [ 141 ]. One of those mechanisms is the modulation of the expression of the cytokines playing a key role in both the adaptive and the innate immune system [ 142 , 143 ].…”
Section: Effects Of Phytogenic Feed Additives On Chickensmentioning
confidence: 99%
“…Adiposity (abdominal fat pad weight relative to body weight) at 8 wk of age in both Fayoumi and Leghorn is approximately half that of broilers (21). All three lines have been characterized extensively with respect to growth, body composition, and immune function (21,49,65,66). Furthermore, these three lines represent the parental strains used to create a panel of advanced intercross lines that can be used for systems genetics studies in chicken (85), comparable with the BXD and Collaborative Cross populations available in mice (19,77,78).…”
mentioning
confidence: 99%